Macroeconomic Policy Directions in West Sulawesi - Sri Utami Permata (Kirana Publisher (KNPub), 2023)
This study was a qualitative descriptive study, which focused on the analysis of West Sulawesi’s macroeconomic policy directions. The data used in this study were the latest data published from the Regional Development Planning Agency of West Sulawesi Province and the Central Bureau of Statistics of West Sulawesi Province in 2022. The results of this study indicated that the direction of regional economic policies was focused on strengthening supply chains and strengthening agricultural, forestry and fisheries business institutions. Furthermore, the tourism sector was also highly considered in improving the regional economy of West Sulawesi, considering that the area has tourism potential that can compete with other provinces. Moreover, policies in the development of superior and cultured human beings were implemented with equal access and quality of education. In addition, the quality of educators and education staff, and the management of education management also need to be prioritized. The health sector also needs to be regulated to increase access and quality of health services.